Comparison of the obesity phenotypes related to monosodium glutamate effect on arcuate nucleus and/or the high fat diet feeding in C57BL/6 and NMRI mice - Matyšková, R; Maletínská, L; Maixnerová, J; Pirník, Z; Kiss, A; Železná, B (Physiological research, 2008)
In this study, susceptibility of inbred C57BL/6 and outbred NMRI mice to monosodium glutamate (MSG) obesity or diet-induced obesity (DIO) was compared in terms of food intake, body weight, adiposity as well as leptin, insulin and glucose levels. MSG obesity is an early-onset obesity resulting from MSG-induced lesions in arcuate nucleus to neonatal mice. Both male and female C57BL/6 and NMRI mice with MSG obesity did not differ in body weight from their lean controls, but had dramatically increased fat to body weight ratio. All MSG obese mice developed severe hyperleptinemia, more remarkable in females, but only NMRI male mice showed massive hyperinsulinemia and an extremely high HOMA index that pointed to development of insulin resistance. Diet-induced obesity is a late-onset obesity; it developed during 16-week-long feeding with high-fat diet containing 60 % calories as fat. Inbred C57BL/6 mice, which are frequently used in DIO studies, both male and female, had significantly increased fat to body weight ratio and leptin and glucose levels compared with their appropriate lean controls, but only female C57BL/6 mice had also significantly elevated body weight and insulin level. NMRI mice were less prone to DIO than C57BL/6 ones and did not show significant changes in metabolic parameters after feeding with high-fat diet.
Keywords: Animals; novorozená zvířata; Eating; Arcuate Nucleus of Hypothalamus; Sodium Glutamate; Female; Phenotype; Age Factors; ženské pohlaví; dietní tuky; druhová specificita; Leptin; Obesity; Animals, Newborn; věkové faktory; nucleus arcuatus hypothalami; Blood Glucose; Adiposity; Mice; Species Specificity; adipozita; Insulin; myši; přijímání potravy; tělesná hmotnost; leptin; obezita; Male; modely nemocí na zvířatech; Disease Susceptibility; Insulin Resistance; inzulinová rezistence; Disease Models, Animal; Body Weight; fenotyp; zvířata; mužské pohlaví; Mice, Inbred C57BL; inzulin; krevní glukóza; Dietary Fats; glutamát sodný; náchylnost k nemoci; myši inbrední C57BL